Personal property law in Nigeria - Mike A.A. Ozekhome (Pretoria University Law Press (PULP), 2020)
This book addresses core issues of personal property law in Nigeria from a comparative perspective. It offers a detailed account of the laws governing personal property and the different lightweight reforms undertaken mainly through case law before the enactment of the Secured Transactions in Movable Assets Act in 2017. The book draws insights from the United States UCC article 9, being unarguably the first law that introduced the concept of modern secured transactions law, and was influential to many common and civilian law systems in reforming their personal property laws. Given that personal property law is fairly new in Nigeria, and also in Africa in general, the main aim of the book is to provide judges and academic researchers with a rich collection of tested solutions from jurisdictions that have experimented with modern secured transactions law for several decades. The primary and secondary works that were referenced in the book have tracked the different epochal shifts in legal thinking and their significances. This may assist scholars and judges in Nigeria to come up with bespoke interpretations of the Act and solutions to underlying problems on credit and security, that will satisfy the local conditions as opposed to copying the unaltered solutions from the United States and other advanced systems.